17
After collecting like terms, (3 - 5x - 5 - 12x) reduces to (-2 - 17x).
12x^3+17x^2+5x=0x(12x^2+17x+5)=0x(x+1)(12x+5)=0x=0x=-1x=-5/12
24x^3 + 72x2 + 30x = 6x*(4x^2 + 12x + 5)=6x*(2x + 1)*(2x + 5)
For example: 9x2-25 = (3x-5)(3x+5) but this only applies to negative expressions it wouldn't apply to 9x2+25
9x2 + 9x - 10 =(3x - 2)(3x + 5)
30+12x = 6(5+2x)
x2-12x+35 = (x-5)(x-7)
(2x - 1)(6x + 5)
If you mean: x2-12x+35 then it is (x-7)(x-5) when factored
Factor: x3 - 12x2 + 35x 1. Factor out a x: x(x2 - 12x + 35). 2. Factor x2 - 12x + 35 which is (x-5)(x-7). 3. Answer: x(x-5)(x-7).
6x^2(2x + 5)
12x-17x = -5
(3x + 5)(3x^2 + 4)
12x + 5 - 2x =(12x - 2x) + 5 =10x + 5 =5 (2x + 1)
5/4x+7/12x is the same as 15/12x+7/12x = 21/12x
When x = 5, 12x = 12*5 = 60.